Towards the understanding of genetic and morphological variations of a highly abundant seaweed-associated marine invertebrate - Longo, Pedro Augusto dos Santos; Azevedo-Silva, Marianne; Mansur, Karine Ferreira Ribeiro; Marinho, Thais Aparecida; Madeira, André Guilherme [UNESP]; Souza, Anete Pereira de; Hirota, Shun K.; Suyama, Yoshihisa; Mori, Gustavo Maruyama [UNESP]; Leite, Fosca Pedini Pereira (Elsevier, 2024)
Unraveling the patterns of genetic structure and demographic history of marine species, as well as the factors that shape their genetic variations, is fundamental for informing conservation strategies for species and their environments. In this work, we investigate the current population structure and historical demographic patterns of the conspicuous seaweed-associated amphipod Hyale niger at a fine spatial scale in the subtropical SW Atlantic coast, in Brazil, by using both genome-wide and mitochondrial DNA markers. We also investigate how geographic distance, current oceanographic conditions, and variations in a key morphological trait contribute to the genetic variability of the amphipod. We observed an evident population genetic structure, even at a fine spatial scale, although genetic differentiation was lower than our expectations for a benthic direct brooder. Demographic history inferences were consistent across populations and showed two major demographic expansions on interglacial periods during the late Pleiostocene, before and after the last glacial maximum. We also demonstrated that isolation-by-environment (IBE) was the main driver of genetic differentiation, although we could not separate it from the effects of isolation-by-distance (IBD). Among environmental factors, nutrient concentrations in seawater were most relevant for explaining genetic structure. In addition, our data suggest that morphological variation in gnathopod 2 structure of males were not genetic-related and were probably plastic as a response to variations in macroalgae frond size. Our study reinforces the importance of using multiple molecular markers and analytical approaches to unveil patterns and processes generating genetic variation in natural populations.

Desvendar os padrões de estrutura genética e a história demográfica de espécies marinhas, bem como os fatores que moldam suas variações genéticas, é fundamental para embasar estratégias de conservação de espécies e seus ambientes. Neste trabalho, investigamos a estrutura populacional atual e os padrões demográficos históricos de Hyale niger, um anfípode com próxima associação com macroalgas, em uma escala espacial fina na costa subtropical do sudoeste do Atlântico, no Brasil, utilizando polimorfismos de nucleotídeo único (SNPs, do inglês, single nucleotide polymorphism) e um marcador mitocondrial. Também investigamos como a distância geográfica, as variáveis oceanográficas contemporâneas e as variações em um traço morfológico funcionalmente relevante, gnatópode 2, contribuem para a variabilidade genética de H. niger. Observamos uma estrutura genética populacional evidente, mesmo em uma escala espacial fina, embora a diferenciação genética tenha sido menor do que nossas expectativas para um organismo bentônico com desenvolvimento direto. As inferências de história demográfica foram consistentes entre as populações e mostraram duas grandes expansões demográficas em períodos interglaciais durante o Pleistoceno tardio, antes e após o Último Máximo Glacial. Demonstramos também que o isolamento-por-ambiente (IBE, do inglês, Isolation-by-environment) foi o principal impulsionador da diferenciação genética, embora não tenhamos conseguido separá-lo dos efeitos do isolamento-por-distância (IBD, do inglês, Isolation-by-distance). Entre os fatores ambientais, as concentrações de nutrientes na água do mar foram as mais relevantes para explicar a estrutura genética. Além disso, nossos resultados sugerem que a variação morfológica na estrutura do gnatópode 2 de machos não esteja relacionada com a variação genética observada e seja provavelmente plástica, como resposta a variações no tamanho das frondes das macroalgas. Nosso estudo reforça a importância do uso de múltiplos marcadores moleculares e abordagens analíticas para desvendar padrões e processos geradores de variação genética em populações naturais.
Rumo à compreensão das variações genéticas e morfológicas de um abundante invertebrado marinho associado a macroalgas
Keywords: Genômica da paisagem marinha; Morfometria geométrica; Anfípode; Macroalgas; Citocromo C Oxidase I; Polimorfismo de nucleotídeo único; Seascape genomics; Geometric morphometrics; Amphipoda; Macroalgae; COI; SNP